Accuracy in navigated percutaneous sacroiliac screw fixation: a systematic review and meta-analysis - R. A. Haveman; L. Buchmann; P. C. Haefeli; F. J.P. Beeres; R. Babst; B.-C. Link; B. J.M van de Wall (BMC Surgery)
Abstract Introduction Percutaneous sacroiliac screw fixation of pelvic fragility fractures is increasingly being used to maintain mobility and reduce pain in the elderly patient population. Traditionally, this is performed using 2D fluoroscopy. Several newer, navigated techniques have emerged that may further facilitate this procedure. It, however, remains unclear whether there is a benefit regarding accuracy, radiation exposure and complications of these new navigation techniques when compared to the traditional 2D fluoroscopy. Methods A systematic review and meta-analysis were performed. PubMed, CENTRAL and Embase were searched for both randomized controlled trials and observational studies comparing new navigation techniques to 2D fluoroscopy for percutaneous sacroiliac screw fixation. Effect estimates were pooled (random effects) and presented as odds ratio, mean difference and standardized mean difference with a 95% confidence interval. Results 19 studies were included. The 2D fluoroscopy group had 642 patients and the new navigation group 663 patients. Accuracy was significantly higher in the new navigation group (OR 2.44, 95% CI 1.53–3.90), especially O-Arm, 3D CT and Robotic navigation. On average, accuracy was 82% in the 2D group and 92% in the new navigation group, which was significant. Also, fluoroscopy time (MD 71.89 s, 95% CI 51.37–92.41) and frequency (MD 17.22 images in total, 95% CI 7.73–26.70) were significantly reduced in the new navigation group. Complications are acceptably low, however, poorly reported in both groups. Conclusion This meta-analysis demonstrated a higher accuracy, lower fluoroscopic frequency and time for new navigation techniques compared to 2D fluoroscopy. More advanced navigation techniques, such as 3D CT and robotic navigation, appeared to be even better.